The long and short-run determinants of workers' remittances to Barbados - Campbell, Trevor (2006)
Uses an error correction model to identify long and short run determinants of workers remittances in Barbados. Concludes that remittances are influenced by real foreign and local income, the real exchange rate and the unemployment rate while in the short run, remittances are impacted upon by real foreign income and the unemployment rate.